Probing the dual burden: assessing psychological distress and substance use among female sex workers in Sonagachi, Kolkata, West Bengal, India - Bhattacharya, Monali; Chandrasekaran, Varalakshm; Arhanthabailu, Praveen; Ashok, Lena (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Psychological distress and substance use is a global public health problem. Understanding the mental distress and substance use regarding female sex workers is crucial which is noticeably lacking in India. The authors of this study investigate the prevalence of psychological distress and substance use among female sex workers in Sonagachi.Methods. Using convenience sampling 149 participants were invited to participate. Tools included socio-demographic proforma, alcohol use disorder identification test to assess the risk of alcohol consumption and patient health questionnaire used to assess anxiety and depression.Results. Overall, 52.4% reported psychological distress and 66.1% of participants were found to use substances. The factors associated with psychological distress are marital status, education level and number of children. Education, sex under the influence of substances, and number of years working predicted a higher likelihood of substance use such as tobacco, cannabis and alcohol. Additionally, psychological distress was more significant among women who were married, worked for more than 5 years, were forced to enter the sex trade and used condoms inconsistently.Conclusion. Education, sex under the influence of alcohol, number of years working, marital status, age of working, reason for sex work and condom use emerged as significant predictors of use of tobacco and cannabis, risk of alcohol consumption and psychological distress.